Chromosomal mapping of H3 histone and 5S rRNA genes in eight species of Astyanax (Pisces, Characiformes) with different diploid numbers: Syntenic conservation of repetitive genes - Piscor, Diovani [UNESP]; Parise-Maltempi, Patricia Pasquali [UNESP] (Canadian Science Publishing, 2016)
The genus Astyanax is widely distributed from the southern United States to northern Patagonia, Argentina. While cytogenetic studies have been performed for this genus, little is known about the histone gene families. The aim of this study was to examine the chromosomal relationships among the different species of Astyanax. The chromosomal locations of the 5S rRNA and H3 histone genes were determined in A. abramis, A. asuncionensis, A. altiparanae, A. bockmanni, A. eigenmanniorum, A. mexicanus (all 2n = 50), A. fasciatus (2n = 46), and A. schubarti (2n = 36). All eight species exhibited H3 histone clusters on two chromosome pairs. In six species (A. abramis, A. asuncionensis, A. altiparanae, A. bockmanni, A. eigenmanniorum, and A. fasciatus), syntenic clusters of H3 histone and 5S rDNA were observed on metacentric (m) or submetacentric (sm) chromosomes. In seven species, clusters of 5S rDNA sequences were located on one or two chromosome pairs. In A. mexicanus, 5S rDNA clusters were located on four chromosome pairs. This study demonstrates that H3 histone clusters are conserved on two chromosome pairs in the genus Astyanax, and specific chromosomal features may contribute to the genomic organization of the H3 histone and 5S rRNA genes.
Keywords: Astyanax schubarti; FISH; Karyotype evolution; Mexican blind cavefish; Repetitive DNAs